Visible light-induced synthesis of conjugated poly(phenylene butadiynylene) by a combination of Halide abstraction and coupling reactions - ÖZDEMİR, MÜCAHİT (My University, 2023)
This study describes a simple and efficient method for synthesizing conjugated poly(phenylene butadiynylene) (PPB)polymers using photo-induced radical homocoupling. The approach involves irradiating 1,4-bis(bromoethynyl)benzene with visible light in the presence of dimanganese decacarbonyl (Mn2(CO)10), which acts as a radical generator by abstracting halides and promoting subsequent radical coupling reactions. The resulting conjugated PPB exhibited a remarkable red shift, and the optical band gap decreased from −2.76 to −2.27 eV. A similar effect was observed in the electrochemically measured oxidation potential; the highest occupied molecular orbital position regressed from −6.06 to −5.69 eV. Transmission electron microscopy and atomic force microscopy measurements revealed the self-organization of the polymers to planar 2D nanorods, and the 2D structures of the polymers were further supported by density functional theory calculations. Moreover, the surface area of the polymer was found to be 53.61 and 30.69 m2/g according to Brunauer-Emmett-Teller and Barrett-Joyner-Halenda methods, respectively.
Keywords: Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Polimer Karakterizasyonu; İnorganik Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Characterization of Polymers; Inorganic Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; KİMYA, İNORGANİK VE NÜKLEER; POLİMER BİLİMİ; KİMYA, ORGANİK; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; CHEMISTRY, INORGANIC & NUCLEAR; POLYMER SCIENCE; CHEMISTRY, ORGANIC; MATERIALS SCIENCE, MULTIDISCIPLINARY; Organik Kimya; Fizik Bilimleri; Polimerler ve Plastikler; İnorganik kimya; Malzeme Kimyası; Organic Chemistry; Physical Sciences; Polymers and Plastics; Materials Chemistry